Aplikasi Pembiayaan di Bank Syariah - Ahmad Dahlan (Al-Manahij: Jurnal Kajian Hukum Islam, 2020)
The aplication of Syariah bank financial which is based on profit and loss sharing, known as margin profit sharing, seems facing many challenges. From the financing side, the obstacles are asymmetric information problem, side streaming, adverse selection, and moral hazard. The indirect obstacles are the sociological aspect, such as a domination of capitalist system in banking and the non optimum human resources.